Differences between CSS Grid and CSS Flexbox - Kolomoyets, D. A.; Nazarov, Y. M. (ТДАТУ, 2021)
Grid is for the skeleton of the site, Flexbox is for the content. We recommend that you stick to this order. And as you work with these two properties, you yourself will begin to feel in which cases this or that technology is more suitable.
Keywords: layout; web page